Bulleyaconitine A Inhibits Visceral Nociception and Spinal Synaptic Plasticity through Stimulation of Microglial Release of Dynorphin A - Huang, Sheng-Nan (Neural plasticity, 2020)
Copyright © 2020 Sheng-Nan Huang et al.